Pengaruh Olahraga Tim Terhadap Keterampilan Sosial Dan Kesehatan Mental Anak SD Muhammadiyah 5 Pekanbaru - Nazirun, Novia; Sari, Merlina (UNIB Press, 2025)
This study aims to analyze the effect of team sports activities on improving social skills and mental health of elementary school students. The background of this study is based on the view that physical education does not only focus on developing physical abilities, but also plays an important role in character formation, social skills, and psychological well-being of students. The research method used was a quasi-experimental design with a one-group pretest–posttest design. The subjects consisted of 30 students of Muhammadiyah 5 Elementary School, Pekanbaru, selected through a purposive sampling technique. The research instruments included a social skills observation sheet and a mental health questionnaire that had been tested for validity and reliability. Data analysis was conducted using a Paired Sample t-test to compare the results before and after treatment. The results showed a significant increase in social skills (from an average of 65.2 to 82.6) and mental health (from an average of 63.5 to 80.4) with a p-value <0.01. These findings prove that participation in team sports activities can improve students' ability to work together, interpersonal communication, and psychological well-being. Thus, the integration of team sports activities in physical education learning can be an effective strategy in forming students' social and mental character holistically.